Increased Phenotype Severity Associated with Splice-Site Variants in a Hungarian Pediatric Neurofibromatosis 1 Cohort: A Retrospective Study - Klára Veres; Benedek Nagy; Zsófia Ember; Judit Bene; Kinga Hadzsiev; Márta Medvecz; László Szabó; Zsuzsanna Zsófia Szalai (Biomedicines)
Background: Neurofibromatosis type 1 (NF1) is a complex neurocutaneous disorder caused by pathogenic variants in the NF1 gene. Although genotype–phenotype correlation studies are increasing, robust clinically relevant correlations have remained limited. Methods: We conducted a retrospective analysis of data obtained from a cohort of 204 Hungarian individuals, with a mean age of 16 years (age range: 1–33 years). The data were collected over 15 years. Results: Among the cohort of 204 patients, 148 subjects fulfilled ≥2 criteria established by the National Health Institute. Genetic testing was performed in 70 patients, with an 82.8% detection rate, of which 13 patients were excluded. Among the remaining 45 pathogenic variants, 17 (37.7%) frameshift, 11 (24.4%) nonsense, 8 (17.8%) splice-site, 4 (8.9%) missense mutations, and 5 (11.11%) copy number variations (CNVs) were detected. Café-au-lait macules were present in all patients (100%). Intracranial malformations were the second most common feature (55.6%), followed by Lisch nodules (35.6%), neurofibromas (33.3%), and skeletal abnormalities (31.1%). Conclusions: In our cohort, patients with splice-site variants (8/45, 17.8%) demonstrated a notably more severe phenotype compared to findings reported in other studies, with a high prevalence of plexiform neurofibromas (37.5%), intracranial findings (62.5%), skeletal abnormalities (50%), Lisch nodules (50%), and even pseudarthrosis (25%). Correlating with the literature, missense variants represented a mild phenotype, while patients with microdeletion syndrome revealed a more severe phenotype.